Identification of Salmonella enterica Serovar Typhimurium Genes Important for Survival in the Swine Gastric Environment - Bearson, Shawn M. D. (American Society for Microbiology, 2006)
Since the stomach is a first line of defense for the host against ingested microorganisms, an ex vivo swine stomach contents (SSC) assay was developed to search for genes important for Salmonella enterica serovar Typhimurium survival in the hostile gastric environment. Initial characterization of the SSC assay (pH 3.87) using previously identified, acid-sensitive serovar Typhimurium mutants revealed a 10-fold decrease in survival for a phoP mutant following 20 min of challenge and no survival for mutants of rpoS or fur. To identify additional genes, a signature-tagged mutagenesis bank was constructed and screened in the SSC assay. Nineteen mutants were identified and individually analyzed in the SSC and acid tolerance response assays; 13 mutants exhibited a 10-fold or greater sensitivity in the SSC assay compared to the wild-type strain, but only 3 mutants displayed a 10-fold or greater decrease in survival following pH 3.0 acidic challenge. Further examination determined that the lethal effects of the SSC are pH dependent but that low pH is not the sole killing mechanism(s). Gas chromatography analysis of the SSC revealed lactic acid levels of 126 mM. Upon investigating the effects of lactic acid on serovar Typhimurium survival in a synthetic gastric fluid, not only was a concentration- and time-dependent lethal effect observed, but the phoP, rpoS, fur, and pnp genes were identified as involved in protection against lactic acid exposure. These studies indicate a role in gastric survival for several serovar Typhimurium genes and imply that the stomach environment is defined by more than low pH.